Comparative Clinical Signs of Herpetic Infection Coupled with HIV Infection - Malika Daminova1, Gulchekhra Makhkamova2, Shakhnoza Abzalova3, Abdusamat Valiyev4, Surayyo Ikramova5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The article represents the results of the observation oft he comparative clinical examination of herpeticinfection coupled with HIV infection in 57 children aged 1 to 15 years. There have been 41 boys (71,93%)and 16 girls(28,07%). The comparison group included 23 children oft he same age infected with HIV withoutherpetic infection.The following laboratory research method have been used: a general analysis of blood, urine, feces, thestudy of the immune status, level of CD4 cells; Serological: by ELISA method antibodies to CMV and HSV(Herpes Simplex Virus) have been detected in blood. The results obtained indicate that coexisting diseaseswith the formation of complications and immunodeficiency development have been worsening the course ofherpetic infection in HIV infected children and leading to a severe relapsing course.